(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to evaluate the quality of library, informational, and administrative services and their role in enhancing scientific research at the university library of Umm Al-Qura University, assessing how well they meet students’ needs. The sample consisted of 907 postgraduate students from the College of Education. Data was collected using a questionnaire as a research tool, and the descriptive method was applied. The study’s key findings indicate overall satisfaction with the quality of library services, particularly in research guidance, research services, and facilities. However, there is a need to improve library hours to better align with students’ schedules and enhance the updating of academic resources. The availability of electronic resources was widely accepted, yet some students reported a lack of modern sources and insufficient updates. Regarding administrative services, the borrowing process and cataloging system were found to be efficient, but there is room for improvement in response speed to inquiries and technical support. The results also highlight the necessity of enhancing the availability of devices and printers and expediting the registration process. Based on these findings, it is recommended to further develop research services, improve the library environment, and increase the efficiency of technical support and administrative services.